An overview of research methods and topics used in Turkological studies - Sözer, Burak; Sakhi, Zhuldyz (Turkic Studies Journal, 2024)
This study examines the past and current status of scientific research methods and topics used in Turkology. The study’s data were sourced from Scopus, a database of prestigious journals and periodicals in the field of social sciences, and the sample of the study consists of studies conducted in the field of Turkology until 2024. In this context, the keywords ‘Turkish language,’ ‘Turkic,’ ‘Turkology,’ ‘Turcology,’ ‘Turcological,’ and ‘Turkish studies’ were searched together with the keywords ‘Quantitative’ and ‘Qualitative.’ As a result of this search, 413 studies were accessed. To reach a wider sample and to provide a general picture of qualified Turkology studies through the Scopus database, the studies in which the keywords ‘Turkish Language’ ‘Turkic’ and ‘Turkology’ were used in the article title, abstract, and keyword were also included in the study. Since the subject area and keyword range are more general, 3,284 studies were reached within the scope of this review. The bibliometric analysis method was used to obtain up-to-date and quantitative data on the studies conducted in the field, and Voswiever and RStudio programs were used. The findings indicate that the significance attributed to scientific research methods in Turkology has continued to increase in recent years.